Influence of rGO and Preparation Method on the Physicochemical and Photocatalytic Properties of TiO2/Reduced Graphene Oxide Photocatalysts - Agnieszka Wanag (MDPI AG, 2021)
In this study, a series of TiO2/rGO photocatalysts were obtained with a two-step procedure: a solvothermal method and calcination at 300–900 °C in an argon atmosphere. It was noted that the presence of rGO in photocatalysts had an important role in the changes in crystallite size and specific surface area. In TiO2/rGO samples, different surface functional groups, such as C−Cgraph, C−Caliph, C−OH, C=O, and CO(O), were found. It was observed that rGO modification suppressed the anatase-to-rutile phase transformation. The photocatalytic activity of the obtained nanomaterials was investigated through the decomposition of methylene blue under UV and artificial solar light irradiation. It was found that the adsorption degree played an important role in methylene blue decomposition. The experimental results revealed that TiO2/rGO samples exhibited superior removal efficiency after calcination for methylene blue compared toTiO2 without rGO, as well as a commercial photocatalyst KRONOClean 7000. It was noted that photocatalytic activity increased with the increase in the calcination temperature. The highest activity was observed for the sample calcined at 700 °C, which consisted of 76% anatase and 24% rutile. This study clearly demonstrated that TiO2/rGO samples calcined in argon can be used as efficient photocatalysts for the application of methylene blue decomposition.